SQL for dummies - Taylor, Allen G. (--For dummies., 2006)
Written in the friendly 'Dummies' style, this book covers the core features of the SQL language and shows programmers and Web developers how to use SQL to build relational databases and extract valuable information from them. Topics covered include how to use SQL to structure a DBMS and implement a database design, secure a database, and retrieve information.